Mediating Role of Boredom in the Workplace on Turnover Intention: A Proposed Framework - Micheal, Teng; Zaiton, Hassan; Mark, Kasa; Nik Norsyamimi, Md Nor; Nur Fatihah, Abdullah Bandar; Rusli, Ahmad (Human Resource Management Academic Research Society, 2020)
Boredom in the workplace is commonly described as one of the negative and widespread phenomenawhere its increasing trend can be seen among employees on all occupational levels. However, the number of investigations performed on the occurrence of boredom in the eastern countries is limited. This study conceptualizes the causal and consequences of boredom in the workplace underpinned bythe Job Demands-Resources (JD-R) theory. Subsequently, it postulates that boredom among employees occurs due to work-related characteristics (i.e.: job demands, job resources) and individual personality traits, as well as time orientation cultural dimension, which may lead to their turnover intention. Furthermore, several hypotheses are proposed in this study. This paper provides several empirical contributions by highlighting the tendency of boredom to occur in the workplace which may leads to the turnover intention. By determining its antecedents, boredom in the workplace can be curbed and the turnover intention can be prevented in a more practical way.